Cytomorphological features of salivary gland lesions based on the Milan system of reporting in a tertiary care center - Chandrakoshi, Gautam; Sanjuna D,; Patidar, Ajay; Singh, Nikita (Asian Journal of Medical Sciences, 2022)
Background: Fine-needle aspiration cytology (FNAC) of the salivary glands is a well-established technique that aids in pre-operative identification of abnormalities and to distinguish between neoplastic and non-neoplastic salivary gland lesions. Milan system for reporting of salivary gland cytology uses a standardized tiered system for categorization of salivary gland lesions. Aims and Objectives: The present research was aimed to study the prevalence of various salivary gland lesions cytologically and classify them based on the Milan system. Materials and Methods: The current retrospective descriptive study was done in the Department of Pathology, Shyam Shah Medical College, Rewa, M.P. A total of 57 FNAC slides were retrieved, re-examined, and re-classified according to the Milan system. Results: In the present study, a total of 57 cases of salivary gland lesions were included and categorized under the Milan system of salivary gland cytology. 5.3% of the smears in our study were non-diagnostic (Category I). The most common category was IVa comprising benign neoplastic lesions with 36.8%. Non-neoplastic lesions (Category II) were seen in 24.6% cases, whereas 14% of the lesions belonged to category IVb (suspicious for malignancy). Malignant lesions (Category VI) comprised 8.8% of all the cases. Conclusion: The most common and least common category of salivary gland lesion was Category IVa and Category IVb, respectively. The adoption of Milan classification system for reporting salivary gland FNAC is a critical step in categorizing these lesions for risk stratification and enhancing the communication among clinicians and pathologists, the ultimate result being improved patient care and management.